EVALUATION OF THE BOOK "UNSKILLED JOBS IN WEST KALIMANTAN" AS AN EXTENSIVE READING MATERIAL FOR TANJUNGPURA UNIVERSITY STUDENTS - Fergina, Ana (Jurnal Visi Ilmu Pendidikan, 2024)
The use of books by students needs to be checked and evaluated periodically to see the book's quality. The book "Unskilled Jobs in West Kalimantan" was assessed to catch readers' responses in the context of the physical appearance of the book and its content. The research was carried out by distributing a mixed questionnaire containing book evaluation and understanding of the books read. Based on the research results, readers responded positively to the book's physical aspects, including layout, design, and cover. Apart from that, the assessment of the book's contents in terms of diction also received a positive response. Readers understand the reading in the book more quickly in a short time. This book is designed for intermediate-level readers. It can be concluded that the book Unskilled Jobs in West Kalimantan meets readers' expectations at the intermediate level.